Population genomic analyses of RAD sequences resolves the phylogenetic relationship of the lichen-forming fungal species Usneaantarctica and Usneaaurantiacoatra - Grewe, Felix (MycoKeys, 2018)
Abstract. Neuropogonoid species in the lichen-forming fungal genus Usnea exhibit great morphological variation that can be misleading for delimitation of species. We specifically focused on the species delimitation of two closely-related, predominantly Antarctic species differing in the reproductive mode and representing a so-called species pair: the asexual U.antarctica and the sexual U.aurantiacoatra. Previous studies have revealed contradicting results. While multi-locus studies based on DNA sequence data provided evidence that these two taxa might be conspecific, microsatellite data suggested they represent distinct lineages. By using RADseq, we generated thousands of homologous markers to build a robust phylogeny of the two species. Furthermore, we successfully implemented these data in fine-scale population genomic analyses such as DAPC and fineRADstructure. Both Usnea species are readily delimited in phylogenetic inferences and, therefore, the hypothesis that both species are conspecific was rejected. Population genomic analyses also strongly confirmed separated genomes and, additionally, showed different levels of co-ancestry and substructure within each species. Lower co-ancestry in the asexual U.antarctica than in the sexual U.aurantiacoatra may be derived from a wider distributional range of the former species. Our results demonstrate the utility of this RADseq method in tracing population dynamics of lichens in future analyses.